Small bowel obstruction SBO after TAPP repair caused by a self-anchoring barbed suture device for peritoneal closure: case report - Tagliaferri, Eugenio M (J Surg Case Rep, 2018)
A 50-year-old man underwent laparoscopic hernia repair for a groin hernia, presenting acute abdominal pain and bowel obstruction syndrome 1 day post surgery. Diagnostic laparoscopy was performed at postoperative the day after the hernioplasty and a volvulus was found. The residual end of the barbed V-LOC adopted in the peritoneal closure was incidentally hooked to the mesentery and caused a small bowel obstruction as a volvulus. The redundant V-LOC strand was released and cut superficial to the peritoneum. A detorsion of volvulus was preformed. Neither bowel ischemia nor significant bowel injury was noted. The following day he was discharged without complication. The residual ‘free’ barbel suture in the peritoneal cavity invited adhesion formations and subsequently the Bowel obstruction.